1991
DOI: 10.1016/0014-5793(91)80675-s
|View full text |Cite|
|
Sign up to set email alerts
|

The complete amino acid sequence of ribonuclease from the seeds of bitter gourd (Momordica charantia)

Abstract: The complete amino acid sequence of ribonuclease (RNase MC) from the seeds of bitter gourd (Motttordica ch=anria) has been determined, This has been achieved by the sequence analysis of peptides derived by enzymatic digestion with trypsin. lysylendopeptidase. and chymotrypsin, as well as by chemical cleavage with cyanogen bromide. The protein contains 191 amino acid residues and has a calculated molecular mass of 21259 Da.Comparison of this sequence with sequences of the fungal RNases. RNase T2, and RNase Rh, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
31
0

Year Published

1993
1993
2001
2001

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(31 citation statements)
references
References 16 publications
0
31
0
Order By: Relevance
“…Taylor et al (1993) have shown that mRNAs with homology to P. hybrida and N. alata S-RNases are expressed in flowers of Arabidopsis thaliana. Other related RNase sequences are found in tomato (Jost et al, 1991), Momordica charantia (Ide et al, 1991), and fungi (Horiuchi et al, 1988;Kawata et al, 1988). The S-RNases seem clearly to be related to a larger family of RNase proteins that have various roles in different plants and plant tissues.…”
Section: Organ-specific Expression Of Gene Fusionsmentioning
confidence: 95%
See 1 more Smart Citation
“…Taylor et al (1993) have shown that mRNAs with homology to P. hybrida and N. alata S-RNases are expressed in flowers of Arabidopsis thaliana. Other related RNase sequences are found in tomato (Jost et al, 1991), Momordica charantia (Ide et al, 1991), and fungi (Horiuchi et al, 1988;Kawata et al, 1988). The S-RNases seem clearly to be related to a larger family of RNase proteins that have various roles in different plants and plant tissues.…”
Section: Organ-specific Expression Of Gene Fusionsmentioning
confidence: 95%
“…All of the style-expressed gametophytic S-alleles that have been cloned to date show homology to a class of fungal RNases (Horiuchi et al, 1988;Kawata et al, 1988;McClure et al, 1989;Clark et al, 1990;Ioerger et al, 1991) as well as to related RNases from self-compatible species (Ide et al, 1991;Jost et al, 1991;Taylor et al, 1993). Furthermore, the S-locus proteins have RNase activity in vitro Gray et al, 1991;Singh et al, 1991) and have been renamed S-RNases to reflect this function.…”
mentioning
confidence: 99%
“…3) The latter enzymes are known to be induced by phosphate deprivation [Jost et al,4) Bariola et al 5) ], in the case of senescence [Lers et al 6) ], and exist in the seeds probably for defense [Ide et al, 7) Rojo et al 8,9) ]. In terms of the evolutional change of plant RNases, knowledge is limited to those plants belonging to Dicotyledoneae, except for barley.…”
mentioning
confidence: 99%
“…In terms of the evolutional change of plant RNases, knowledge is limited to those plants belonging to Dicotyledoneae, except for barley. 10) These include several plants of Solanaceae [tomato, 4,11) and tobacco, 3,12) petunia 13) and a kind of potato 14) ], Cucurbitaceae [bitter gourd, 7) cucumber, 8) melon 9) ], Rosacease [pear 15) ], Arabidopsis, 16) Zinnia elegance, 17) Panax ginnseng 18) and others. In this report, we will describe the amino acid sequence of an RNase from rice bran (Oryza sativa) which is a member of Monocotyledoneae, and its enzymatic properties.…”
mentioning
confidence: 99%
“…They were RNase MCI from Momoridica charantia 10 ) and RNase LCI from Luffa cylindrica. 1 0) Their primary structures were very similar to those of tomato extracellular RNase and N. alata RNase.…”
mentioning
confidence: 99%